Blood basophil activation is a reliable biomarker of allergic bronchopulmonary aspergillosis in cystic fibrosis. Issue 1 (19th November 2015) - Gernez, Yael; Walters, Jeffrey; Mirković, Bojana; Lavelle, Gillian M.; Colleen, Dunn E.; Davies, Zoe A.; Everson, Cassie; Tirouvanziam, Rabindra; Silver, Elana; Wallenstein, Sylvan; Chotirmall, Sanjay H.; McElvaney, Noel G.; et al.
The diagnosis of cystic fibrosis (CF) patients with allergic bronchopulmonary aspergillosis (ABPA) is clinically challenging, due to the absence of an objective biological test. Since blood basophils play a major role in allergic responses, we hypothesised that changes in their surface activation pattern discriminate between CF patients with and without ABPA. We conducted a prospective longitudinal study (Stanford cohort) comparing basophil activation test CD203c levels by flow cytometry before and after activation with Aspergillus fumigatus allergen extract or recombinant Asp f1 in 20 CF patients with ABPA (CF-ABPA) and in two comparison groups: CF patients with A. fumigatus colonisation (AC) but without ABPA (CF-AC; n=13) and CF patients without either AC or ABPA (CF; n=12). Patients were tested every 6 months and when ill with pulmonary exacerbation. We also conducted cross-sectional validation in a separate patient set (Dublin cohort). Basophil CD203c surface expression reliably discriminated CF-ABPA from CF-AC and CF over time . Ex vivo stimulation with A. fumigatus extract or recombinant Asp f1 produced similar results within the Stanford (p<0.0001) and the Dublin cohorts. CF-ABPA patients were likelier to have elevated specific IgE to A. fumigatus and were less frequently co-infected with Staphylococcus aureus . Basophil CD203c upregulation is a suitable diagnostic and stable monitoring biomarker of ABPA in CF. Blood basophil surface CD203c level is a method to diagnose ABPA in CF, and study phenotypes, therapy and management http://ow.ly/Sc8zr